Novel Design of a Vertical Axis Hydrokinetic Turbine âStraight-Blade Cascaded (VAHTâSBC): Experimental and Numerical Simulation - Ridho Hantoro; Erna Septyaningrum (Institute for Research and Community Services, Institut Teknologi Bandung, 2018)
A promising technology to reduce dependency on fossil fuels is hydrokinetic energy conversion using either turbine and non-turbine technology. Hydrokinetic turbine technology is penalized by low efficiency and lack of self-starting. This study involved experimental testing and numerical simulation of a novel hydrokinetic turbine design, called a Vertical Axis Hydrokinetic Turbine â Straight-Blade Cascaded (VAHTâSBC). Three configurations of the design were tested. Model 1 had 3 passive-pitch blades, while Model 2 and Model 3 had 6 and 9 blades respectively, where the outer blades were passive-pitch and the others fixed-blade. Both in the experimental test and in the numerical simulation Model 3 outperformed the other two models. The Cp of Model 3 was 0.42, which is very close to the theoretical Cp for VAHTs (0.45). It worked properly at low TSR. A CFD simulation based on the RANS solver was performed to gain supplementary information for performance investigation. This simulation confirmed that the torque changes because of the change in angle of attack as the turbine rotates. Because they have different numbers of blades, each model has different periodical torque fluctuation patterns. This study verified that utilization of cascaded blades and a passive-pitch mechanism is able to improve turbine performance.